Structural Basis of SARS-CoV-2 and SARS-CoV Antibody Interactions - Gavor, Edem (Trends Immunol, 2020)
The 2019 coronavirus pandemic remains a major public health concern. Neutralizing antibodies (nAbs) represent a cutting-edge antiviral strategy. We focus here on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and SARS-CoV, and discuss current progress in antibody research against rampant SARS-CoV-2 infections. We provide a perspective on the mechanisms of SARS-CoV-2-derived nAbs, comparing these with existing SARS-CoV-derived antibodies. We offer insight into how these antibodies cross-react and cross-neutralize by analyzing available structures of spike (S) glycoprotein–antibody complexes. We also propose ways of adopting antibody-based strategies – such as cocktail antibody therapeutics against SARS-CoV-2 – to overcome the possible resistance of currently identified mutants and mitigate possible antibody-dependent enhancement (ADE) pathologies. This review provides a platform for the progression of antibody and vaccine design against SARS-CoV-2, and possibly against future coronavirus pandemics.